Analysis of University Students’ Mental Health from the Perspective of Occupational Harmony - Yijun Liu; Ruiqi She; Jin Xing (PLoS ONE, 2025)
Background Mental health problems are common among university students. Based on the Model of Occupational Harmony, we investigated the relationship between occupational engagement and mental health among Chinese university students. Methods A mixed methods approach was adopted. A total of 734 Chinese university students responded to online questionnaires: a socio-demographic questionnaire, the Depression Anxiety Stress Scale, the WHOQOL-BREF, and a self-designed Occupational Harmony Questionnaire. Individual interviews with 11 university students and a focus group of four students provided qualitative data. Results Anxiety, depression, and stress were reported by 11.9%, 9.4%, and 2.9% of the participants, respectively. The level of occupational harmony was negatively correlated with depression, anxiety, and stress (p <  .001). The DASS-21 score was significantly different among students who spent different amounts of time on the following activities: exercise, sleep, rest, reflective and consulting activities, study, work, and leisure and entertainment (P < .05). In the context of the COVID-19 pandemic, the key occupational factors contributing to university students’ mental health problems included excessive mental engagement and insufficient physical engagement, excessive active engagement and insufficient quiet engagement, insufficient social engagement, excessive or insufficient Gong (productive) engagement , and insufficient De (virtuous) engagement, Zhi (rational) engagement, and Kang (health maintenance) engagement, lack of coherence within the family, school, social systems, as well as inadequate schedule planning and time management. Conclusions Occupational disharmony is related to university students’ mental health problems. Occupational therapy can promote university students’ mental well-being by enhancing occupational harmony.